2019
DOI: 10.4314/acsj.v27i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of effectiveness marker-assisted gamete selection for multiple disease resistance in common bean

Abstract: Plant breeding is the most cost-effective, practical and environmentally friendly strategy for reducing losses associated with bean diseases, especially in low-input agricultural systems because no additional investment is required from farmers. However, incorporating resistance to one pathogen may not result in a significant change because several diseases co-infection beans at the farm level. Consequently, breeding varieties with multiple disease resistance is a more appropriate, reliable and sustainable app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These efforts have provided molecular tools to accelerate the selection of resistant germplasm through MAS (Meziadi et al., 2017). Recent studies underline the effectiveness of MAS for introgression of multiple disease resistances in breeding programs (Mondo et al., 2019; Rezene et al., 2019). In this study, we identified a set of SNP markers that can be readily used for MAS of BLCrV resistance and could be complementary in the breeding effort against other begomovirus‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have provided molecular tools to accelerate the selection of resistant germplasm through MAS (Meziadi et al., 2017). Recent studies underline the effectiveness of MAS for introgression of multiple disease resistances in breeding programs (Mondo et al., 2019; Rezene et al., 2019). In this study, we identified a set of SNP markers that can be readily used for MAS of BLCrV resistance and could be complementary in the breeding effort against other begomovirus‐related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The crops have dense macro-and micronutrients content (Mibei et al, 2016;Ngugi et al, 2016;Ontita et al, 2016;Ali et al, 2021); can effectively provide solutions to the double malnutrition challenge experienced on the African continent, and proponents have recommended the need to intensify research on traditional crops. However, research has put more focus on crops such as maize, wheat and rice (Mondo et al, 2018;Mwizerwa et al, 2018;Gitari et al, 2019;Odingo, 2019;Owade et al, 2019;Ichami et al, 2020;Jekayinoluwa et al, 2020;Mukami et al, 2020;Malavi et al, 2021;Wagaba et al, 2021). As a result, many of the traditional food crops remain undocumented, and the few documented crops have not been exploited sufficiently to attain their full potential considering all the activities along the food system value chain (Sibanda and Mwamakamba, 2021).…”
Section: Background Informationmentioning
confidence: 99%
“…The crops have dense macro-and micronutrients content (Mibei et al, 2016;Ngugi et al, 2016;Ontita et al, 2016;Ali et al, 2021); can effectively provide solutions to the double malnutrition challenge experienced on the African continent, and proponents have recommended the need to intensify research on traditional crops. However, research has put more focus on crops such as maize, wheat and rice (Mondo et al, 2018;Mwizerwa et al, 2018;Gitari et al, 2019;Odingo, 2019;Owade et al, 2019;Ichami et al, 2020;Jekayinoluwa et al, 2020;Mukami et al, 2020;Malavi et al, 2021;Wagaba et al, 2021). As a result, many of the traditional food crops remain undocumented, and the few documented crops have not been exploited sufficiently to attain their full potential considering all the activities along the food system value chain (Sibanda and Mwamakamba, 2021).…”
Section: Background Informationmentioning
confidence: 99%